Poor semen quality is associated with impaired antioxidant response and acute phase proteins and is likely mediated by high cortisol levels in Brucella-seropositive dromedary camel bulls - Ahmed Saad Ahmed Hassaneen; Anis Anis; Safaa Y. Nour; Rasha Salah Mohamed; Islam M. Wassif; Adel M. El-kattan; Hosny Ahmed Abdelgawad; Ragab H. Mohamed (Scientific Reports)
Abstract Brucellosis in dromedary camel bulls leads to either temporary or permanent loss of fertility. Camel brucellosis is associated with both orchitis and epididymitis. However, the clinical signs of camel brucellosis are not clear as those in cattle. Therefore, this study aimed to diagnose camel brucellosis based on a serological screening using Rose Bengal plate test (RBPT) followed by competitive ELISA. To understand the impact of brucellosis on camel bull fertility, this study aimed to examine the semen characteristics, evaluate the testicular histopathology, examine hormonal profile, antioxidants and acute phase proteins (APP). A total of 150 mature bulls were used in this study. Blood samples were collected for serological, hormonal, and biochemical analysis. This study revealed that 6.6% and 7.3% of the examined bulls were Brucella-seropositive using RBPT and competitive ELISA, respectively. The Brucella-seropositive dromedary bulls showed poor semen quality, pathological changes orchitis, and lower testosterone. Moreover, our findings showed a higher cortisol level, and significant impairments in the measured APP and antioxidants in Brucella-seropositive bulls. In conclusion, the Brucella-seropositive dromedary bulls showed lower fertility due to poor semen quality and lower testosterone levels. Such lower fertility is likely mediated by high cortisol levels, and impaired APP and antioxidants’ defense response.